Radiology plus ileocolonoscopy versus radiology alone in Crohn’s disease: prognosis prediction and mutual agreement - Hye Kyung Hyun (The Korean Journal of Internal Medicine, 2022)
Background/Aims The optimal tools for monitoring Crohn’s disease (CD) are controversial. We compared radiology plus ileocolonoscopy and radiology alone in terms of prognosis prediction and evaluated the agreement between radiologic and ileocolonoscopic findings in patients with CD. Methods Patients with CD who were followed up with computed tomography enterography (CTE) or magnetic resonance enterography (MRE) alone or CTE or MRE plus ileocolonoscopy were retrospectively recruited. Time to relapse was investigated to evaluate the difference in prognosis using the log-rank and Cox regression tests, and the agreement between radiologic and ileocolonoscopic findings was determined using a kappa value. Results A total of 501 patients with CD in clinical remission who underwent CTE or MRE and/or ileocolonoscopy were analyzed. Of these, 372 (74.3%) patients underwent CTE or MRE alone and 129 (25.7%) patients underwent CTE or MRE plus ileocolonoscopy. The cumulative maintenance rate of clinical remission between the two groups was not significantly different (p = 0.526, log-rank test). In multivariate analysis, age <40 years (hazard ratio [HR], 2.756; 95% confidence interval [CI], 1.263 to 6.013) and a history of steroid use (HR, 2.212; 95% CI, 1.258 to 3.577) were found to independently predict an increased risk for clinical relapse in patients with CD in clinical remission. Radiologic and ileocolonoscopic findings had a moderate degree of agreement (κ = 0.401, −0.094 to 0.142). The comparison of agreement between radiologic and ileocolonoscopic findings was the highest in the anastomotic site (κ = 0.749, −0.168 to 0.377). Conclusions Radiology plus ileocolonoscopy was not superior to radiology alone in predicting the prognosis of CD.